Maze warriors - Ahmad Anas, Siti Barirah; Sahbudin, Ratna Kalos Zakiah; Syed Ahmad Abdul Rahman, Sharifah Mumtazah; Shafie @ Musa, Siti Mariam (Universiti Putra Malaysia Press, 2017)
Light travels in a straight line and never curves, but changes its direction through reflection. The light ray that strikes a surface is called the incident ray, while the one that bounces off is the reflected ray. All reflected light obeys the Snell’s Law, that the angle of incidence equals the angle of reflection.